Communication between Parents and Teachers of Special Education Students: A Small Exploratory Study of Reddit Posts - Marisa Alise Madsen; Dag Øivind Madsen (Social Sciences, 2022)
Communication between teachers and parents is an important research topic in the field of special education. Although this type of communication is fraught with challenges such as conflict and lack of trust, there are also some success factors such as collaborative two-way communication and the use of appropriate technologies to facilitate communication. In this paper, we set out to explore this topic in more depth, by examining the experiences of parents and teachers of special-needs students when it comes to communication. A small exploratory qualitative study of social media posts from Reddit is performed. The aim is to shed light on the experiences of parents and teachers. The findings show that both parts of this dyadic relationship have mixed experiences, but the general sentiment is skewed towards the negative. These findings are discussed in relation to the literature on parent-teacher communication.